The Effect of Marketing Capability and Brand Reputation on Brand Loyalty of Tomoro Coffee through Competitive Advantage as a Meditation Variable - Viando, Feterrido Wahyu; Paramitha, Intan Tirzana; Mujanah, Siti; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
The purpose of this research is to analyze the influence of marketing capabilities and brand reputation on competitive advantage and brand loyalty among Tomoro Coffee customers in Surabaya. This study employs a quantitative research design using a cross-sectional method. The sample used in this research consisted of 100 respondents who are Tomoro Coffee customers residing in Surabaya. Sampling was conducted randomly through an online questionnaire using a Likert scale. Data analysis was carried out using the Structural Equation Modeling ( SEM ) approach with the Partial Least Squares ( PLS ) methodology. The results of this research indicate that marketing capability and brand reputation have a positive and significant effect on competitive advantage. Competitive advantage, in turn, has a positive and significant effect on brand loyalty. Marketing capability has a negative and insignificant effect on brand loyalty, whereas brand reputation exerts a positive and significant effect on brand loyalty. Furthermore, brand reputation has a significant influence on brand loyalty through competitive advantage as a mediating variable, while marketing capability demonstrates an insignificant effect on brand loyalty through competitive advantage as a mediating variable. The implications of this research suggest that Starbucks and other business actors can enhance their performance measurement systems related to marketing capability, brand reputation, competitive advantage, and brand loyalty. These improvements are essential for maintaining and strengthening their competitive position in the market. Keywords : Marketing Capability, Brand Reputation, Competitive Advantage, Brand Loyalty, Tomoro Coffee